Penerapan Metode PROMETHEE II Dalam Karyawan Terbaik Pada Pusat Penelitian Kelapa Sawit Area Medan - Muhammad Indra Sukmana (STMIK Budi Darma, 2021)
Today's technology is very important for people's daily lives, computerization and information are needed for decision making during the selection and selection of the best candidates for employees. The company is also experiencing difficulties because so many employees will be selected to get holiday gifts abroad. With the decision support system to determine the best employee using the PROMETHEE II method, the company is easier to determine the employees and the weight value of each attribute or alternative with the assessment criteria that have been determined by the company. The design of a decision support system using the PROMETHEE II method in determining the best employees to get holiday prizes abroad in the PPKS Medan area is built with the Visual Basic 2008 programming language, the running system will produce output in the form of employee names that are eligible to get holiday prizes abroad. This system is expected to be able to help companies find out who are the best employees who really deserve a holiday prize abroad.